Non-Enzymatic Glycation in Alzheimer’s and Parkinson’s Disease: A Molecular Approach to Pathology and Recent Advances - Mohammad Nadeem Khan (International Journal of Molecular Biotechnological Research, 2024)
Non-enzymatic glycation, a biochemical process by which reducing sugars spontaneously bind to proteins, leads to the formation of advanced glycation end-products (AGEs), which have emerged as critical contributors to the pathogenesis of several neurodegenerative diseases, particularly Alzheimer’s disease (AD) and Parkinson’s disease (PD). The accumulation of AGEs can significantly alter protein structure, stability, and function, triggering a cascade of detrimental effects, including increased oxidative stress, heightened neuroinflammation, and the promotion of pathological protein aggregation—hallmarks associated with the progression of these debilitating disorders. This article delves into recent molecular and mechanistic insights into how glycation drives proteomic alterations in AD and PD, examining its impact on neuronal integrity and cellular homeostasis. Additionally, it highlights significant advancements in modern analytical techniques, such as mass spectrometry and advanced proteomic tools, that have been pivotal in elucidating glycation-induced modifications at the molecular level. Emphasis is placed on emerging therapeutic strategies aimed at targeting glycation pathways, including the inhibition of AGE formation, scavenging of reactive intermediates, and the enhancement of cellular repair mechanisms, offering promising avenues for innovative and effective intervention in these neurodegenerative diseases.
Keywords: AGE-RAGE signaling; Advanced glycation end-products (AGEs); Alzheimer’s disease (AD); Oxidative stress; Parkinson’s Disease (PD); neuroinflammation; protein misfolding; proteomics